2018
DOI: 10.1115/1.4040030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inlet Distortion Features on Transonic Fan Rotor Stall

Abstract: The effect of inlet distortion from curved intake ducts on jet engine fan stability is an important consideration for next-generation passenger aircraft such as the boundary layer ingestion (BLI) “silent aircraft.” Highly complex inlet flows which occur can significantly affect fan stability. Future aircraft designs are likely to feature more severe inlet distortion, pressing the need to understand the important factors influencing design. This paper presents the findings from a large computational fluid dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The distortion events that are shown within this work are therefore in the frequency range of interest for the engine instabilities. However, the lower the frequency of the disturbances, the higher is the magnitude required to trigger stall inception [38]. Therefore, it is theorized that the shift towards a lower frequency bands observed with Profile A and Profile B at = 0° may be beneficial for the engine stability.…”
Section: Spectral Analysismentioning
confidence: 99%
“…The distortion events that are shown within this work are therefore in the frequency range of interest for the engine instabilities. However, the lower the frequency of the disturbances, the higher is the magnitude required to trigger stall inception [38]. Therefore, it is theorized that the shift towards a lower frequency bands observed with Profile A and Profile B at = 0° may be beneficial for the engine stability.…”
Section: Spectral Analysismentioning
confidence: 99%
“…The simulations of Page et al [22] support this observation as a notable loss of stability margin was demonstrated when low momentum flow was ingested in the tip region of the fan.…”
mentioning
confidence: 80%
“…Cousins [21] states that the time which is taken for a distortion to convect from the leading edge to the throat of the rotor blade is important in defining the response of the compressor to distortion. However, a typical assumption which is made is that distortions which persists for a duration which is less than the equivalent time for 60° of the rotor revolution are expected to have a negligible impact on fan stability [22]. Similarly, for sufficiently slow variations in intake distortion, the response of the fan is primarily influenced by the spatial distribution of the steady-state flow distortion.…”
Section: B Flow Field Spectral Analysismentioning
confidence: 99%
“…Page et. al [4] calculated the stall inception process with different inlet distortions generated by curved intake ducts. The results provided evidence that the low momentum flow in the tip region leads to damaging instability.…”
Section: Introductionmentioning
confidence: 99%